Spin-state transition in LaCoO 3: direct neutron spectroscopic evidence of excited magnetic states - Podlesnyak, Andrey; Haverkort, Maurits W. (Physical review letters, 2006)
A gradual spin-state transition occurs in LaCoO3 around T∼80-120 K, whose detailed nature remains controversial. We studied this transition by means of inelastic neutron scattering and found that with increasing temperature an excitation at ∼0.6 meV appears, whose intensity increases with temperature, following the bulk magnetization. Within a model including crystal-field interaction and spin-orbit coupling, we interpret this excitation as originating from a transition between thermally excited states located about 120 K above the ground state. We further discuss the nature of the magnetic excited state in terms of intermediate-spin (t52ge1g, S=1) versus high-spin (t42ge2g, S=2) states. Since the g factor obtained from the field dependence of the inelastic neutron scattering is g∼3, the second interpretation is definitely favored.
Die Ziffer "3" im Titel ist tiefgestellt
Gesehen am 08.11.2017